Microalgae-Based Functional Foods: A Blue-Green Revolution in Sustainable Nutrition and Health - Gabriela Andrade-Bustamante; Francisco Eleazar Martínez-Ruiz; Jesus Ortega-García; Prabhaharan Renganathan; Lira A. Gaysina; Muhilan Mahendhiran; Edgar Omar Rueda Puente (Applied Microbiology)
The projected global population of 9.22 billion by 2075 necessitates sustainable food sources that provide health benefits beyond essential nutrition, as the relationship between food biochemistry and human well-being is becoming increasingly significant. Microalgae are simple microscopic organisms rich in various bioactive compounds, such as pigments, vitamins, polyunsaturated fatty acids, polysaccharides, bioactive peptides, and polyphenols, which can be used to develop novel foods with potential health benefits. Bioactive substances offer numerous health benefits, including anti-inflammatory, anticancer, antioxidant, anti-obesity, and heart-protective effects. However, incorporating microalgal biomass into functional food products presents several challenges, including species diversity, fluctuations in biomass production, factors affecting cultivation, suboptimal bioprocessing methods, inconclusive evidence regarding bioavailability and safety, and undesirable flavors and aromas in food formulations. Despite these challenges, significant opportunities exist for the future development of microalgae-derived functional food products. Extensive investigations are essential to overcome these challenges and enable the large-scale commercialization of nutritious microalgae-based food products. This review aims to examine the potential of microalgae as natural ingredients in functional food production, explore the factors limiting their industrial acceptance and utilization, and assess the safety issues associated with human consumption.